The capacity allocation method of photovoltaic and energy storage hybrid system considering the whole life cycle. (1st December 2020) - Li, Junhui; Zhang, Zheshen; Shen, Baoxing; Gao, Zhuo; Ma, Dexuan; Yue, Pengcheng; Pan, Junliang
Abstract: In order to make full use of the photovoltaic (PV) resources and solve the inherent problems of PV generation systems, a capacity optimization configuration method of photovoltaic and energy storage hybrid system considering the whole life cycle economic optimization method was established. Firstly, this paper established models for various of revenues and costs, and establish the capacity allocation model of the photovoltaic and energy storage hybrid system considering the constraints of energy storage system (ESS) charge and discharge power. Secondly, the control strategy of the ESS was designed for the capacity allocation model, including ESS action timing judgment and operation mode selection based on the time-of-use electricity price, which ensures a high degree of matching between the control strategy and the capacity allocation. Finally, Particle swarm optimization was used to solve the capacity optimization configuration model of the photovoltaic and energy storage hybrid system to obtain the optimal configuration of the system. In the calculation example, the characteristics and economics of various PV panels and energy storage cells are compared, and the effects of different ESS on capacity allocation and the impact of different types of income on economics are analyzed, and get the optimal configuration scheme of the PV and ESS hybrid system. The results of calculation examples show that with the capacity allocation method proposed in this paper, the benefit of the photovoltaic and energy storage hybrid system is 1.36 times as its investment cost, and the economic benefits brought by energy conservation and emission reduction account for 22.5% of the total revenue. This means that the economic efficiency can be significantly improved while ensuring the demand of the supply load. At the same time, it has a guiding effect on the capacity allocation of PV energy storage power station. Highlights: Establish a capacity optimization configuration model of the PV energy storage system. Design the control strategy of the energy storage system, including timing judgment and operation mode selection. The characteristics and economics of various PV panels and energy storage batteries are compared.